2009
DOI: 10.1007/s10452-009-9283-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of winter conditions on spring nutrient concentrations and plankton in a large shallow Lake Peipsi (Estonia/Russia)

Abstract: During the study period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…However, also in May an effect of the time of ice break-up and severity of winter on water temperature could be observed. An earlier analysis of a 12-year data set (1997Blank et al, 2009) also showed that water temperatures in May are positively correlated with those in April (r = 0.68, p < 0.001). As a rule, water and air temperatures in June behaved independently of winter conditions.…”
Section: Ice Duration and Water Temperatures In The Months Following mentioning
confidence: 76%
See 2 more Smart Citations
“…However, also in May an effect of the time of ice break-up and severity of winter on water temperature could be observed. An earlier analysis of a 12-year data set (1997Blank et al, 2009) also showed that water temperatures in May are positively correlated with those in April (r = 0.68, p < 0.001). As a rule, water and air temperatures in June behaved independently of winter conditions.…”
Section: Ice Duration and Water Temperatures In The Months Following mentioning
confidence: 76%
“…As water temperature is considered to be one of the most important factors influencing zooplankton abundances in spring in temperate lakes (Swadling et al, 2000;Chen & Folt, 2002;Shatwell et al, 2008;Blank et al, 2009), climatic factors such as an increase in winter/spring air temperature affect the timing of zooplankton spring development (Weyhenmeyer et al, 1999;Mehner, 2000;Gerten & Adrian, 2002;Romare et al, 2005;Wagner & Benndorf, 2007;Richardson, 2008).…”
Section: Zooplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the severity of winter influenced spring nutrient concentrations in Lake Peipsi (Blank et al . ). Altogether such seasonal connections strongly favour previous calls to ‘close the loop’ (Salonen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Similar mechanisms could be responsible for the negative effects of higher spring water temperatures on TP in Lake Peipsi, where the biomass of cladocerans has been found to correlate positively with the sum of daily water temperatures in spring (April, May, June over the 1997-2007 period; Blank et al, 2009). It is likely that PAR in the period after 180 th day was associated with decreasing TP values via the compounding influences from other factors.…”
Section: Discussionmentioning
confidence: 98%